A Hybrid Deep Flux Weakening Algorithm for Five-phase PMSM Based on Deadbeat Predictive Control - Mao, Youwei; Gao, Qiang (2023 IEEE 6th International Electrical and Energy Conference (CIEEC), 2023)
Aiming at the problem that the flux-weakening depth of FIPMSM is not deep, this paper proposes a hybrid deep flux weakening control algorithm based on negative d-axis current compensation combined with MTPV for FIPMSM. In addition, in order to solve the problem that the current loop when adopting PI control is saturated and out of control when the motor just enters the flux weakening stage, the current loop adopts the deadbeat current predictive control based on the Luenberger state observer to realize delay and disturbance compensation. Finally, the effectiveness of the algorithm is verified through experiments, and 2.5 times of flux-weakening based on this algorithm for FIPMSM is achieved.